2017
DOI: 10.21767/2171-6625.1000231
|View full text |Cite
|
Sign up to set email alerts
|

Different Incidences of Acute Bacterial Meningitis in Children of Central Punjab in Pakistan

Abstract: Background: Acute Bacterial Meningitis (ABM) is a serious public health problem demanding early diagnosis, effective treatment, prevention, and control. Approximately 70 percent of meningitis cases occur in children under the age of 5 and in adults over the age of 60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Approximately 70% of cases of meningitis occur in children under the age of 5 years and in adults over the age of 60 [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 70% of cases of meningitis occur in children under the age of 5 years and in adults over the age of 60 [11].…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of ABM cases in the world cause three major pathogens: +LE, Streptococcus pneumoniae (S. pneumonia) and Neisseria meningitidis (N. meningitides). However, the introduction of protein conjugated vaccines against these three pathogens in some countries has changed the epidemiology of bacterial meningitis [3,11,17]. In the United States there is a tendency to reduce morbidity and mortality for pneumococcal and meningococcal meningitis which are associated with the introduction of appropriate vaccination [9].…”
Section: Introductionmentioning
confidence: 99%
“…Acute bacterial meningitis is a recurrent cause of mortality in all age groups, especially in underdeveloped countries [1,2]. Erum et al reported the highest incidence in neonates than other age groups in Pakistan [1]. It is reported as one of the top 10 causes of infection-related deaths worldwide [1].…”
Section: Introductionmentioning
confidence: 99%
“…There are three main causative organisms accounting for over 90% of the world cases of ABM. These are Nesseria meningitidis, Streptococcus pneumonia and Hemophilus influenza type b (Hib) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation of ABM is usually different according to the age of patients, the causative bacteria and the duration of symptoms [2]. Neonates often present with nonspecific symptoms such as irritability, poor feeding, respiratory distress, pale or marble skin and hyper-or hypotonia [3,4].…”
Section: Introductionmentioning
confidence: 99%